Penanaman Konsep Membaca Awal Menggunakan Alat Peraga Berupa Kartu Huruf dalam Mata Pelajaran Bahasa Indonesia di SDN 12 Nan Sabaris - Mimi Suharti Mimi Suharti (Jurnal Konseling dan Pendidikan, 2015)
Learning to read and write at primary school level is the main staple for Indonesian lessons, if students do not have the ability to read and write at an early stage, it will be very difficult for any lesson. Results of preliminary observations at 12 Nan ​​Primary School Sabaris shows that there are some constraints faced by teachers in the learning process. One problem is difficult to instill the concept of reading and writing in students. The purpose of this action research are (1) to determine the extent to which the use of learning resources in the form of cards of letters and syllables and words can influence the level of student ability in assembling verbatim and read (2) to improve the ability of students to practice reading by using the card shared-card teacher said. Data obtained through tests and usage observation guide, the data is processed by a percentage. Results of the analysis of the data obtained in the first cycle of learning success; 61.00%, and the second cycle; amounting to 81.50%. So it showed no increase student learning from the first cycle to the second cycle. Thus the letter card usage can improve the understanding of stringing words and reading in students. This is evident from the enthusiasm with studentsmenyususun verbatim via encrypted card.